A gamma‐ray spectroscopy survey of Omani meteorites. (10th March 2017) - Weber, Patrick; Hofmann, Beda A.; Tolba, Tamer; Vuilleumier, Jean‐Luc
Abstract: The gamma‐ray activities of 33 meteorite samples (30 ordinary chondrites, 1 Mars meteorite, 1 iron, 1 howardite) collected during Omani‐Swiss meteorite search campaigns 2001–2008 were nondestructively measured using an ultralow background gamma‐ray detector. The results provide several types of information: Potassium and thorium concentrations were found to range within typical values for the meteorite types. Similar mean 26 Al activities in groups of ordinary chondrites with (1) weathering degrees W0‐1 and low 14 C terrestrial age and (2) weathering degree W3‐4 and high 14 C terrestrial age are mostly consistent with activities observed in recent falls. The older group shows no significant depletion in 26 Al. Among the least weathered samples, one meteorite (SaU 424) was found to contain detectable 22 Na identifying it as a recent fall close to the year 2000. Based on an estimate of the surface area searched, the corresponding fall rate is ~120 events/10 6  km 2 *a, consistent with other estimations. Twelve samples from the large JaH 091 strewn field (total mass ~4.5 t) show significant variations of 26 Al activities, including the highest values measured, consistent with a meteoroid radius of ~115 cm. Activities of 238 U daughter elements demonstrate terrestrial contamination with 226 Ra and possible loss of 222 Rn. Recent contamination with small amounts of 137 Cs is ubiquitous. We conclude that gamma‐ray spectroscopy of a selection of meteorites with low degrees of weathering is particularly useful to detect recent falls among meteorites collected in hot deserts.